2021
DOI: 10.1038/s41421-021-00274-1
|View full text |Cite
|
Sign up to set email alerts
|

Integrating longitudinal clinical laboratory tests with targeted proteomic and transcriptomic analyses reveal the landscape of host responses in COVID-19

Abstract: The pathophysiology of coronavirus disease 19 (COVID-19) involves a multitude of host responses, yet how they unfold during the course of disease progression remains unclear. Here, through integrative analysis of clinical laboratory tests, targeted proteomes, and transcriptomes of 963 patients in Shanghai, we delineate the dynamics of multiple circulatory factors within the first 30 days post-illness onset and during convalescence. We show that hypercortisolemia represents one of the probable causes of acute l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 91 publications
2
15
0
Order By: Relevance
“…Additionally, in terms of individual genes in the turquoise module, we identified hub-high traffic genes such as UTP14A ( 398 ), RUVBL2 ( 139 ), PRKCD ( 280 , 399 ), KEAP1 ( 400 402 ), CEBPA (TF) ( 403 ), RPL26L1 ( 404 ), PTPN6 ( 255 ), PPARA (TF) ( 405 ), TNFRSF1A ( 406 408 ), IKBKB ( 275 , 409 ), TFEB (TF) ( 410 , 411 ), PSMD4 ( 412 ), and ARHGAP1 ( 413 ), important components in immunopathogenesis of SARS-CoV-2. For example, the TNF receptor superfamily member 1A ( TNFRSF1A ) hub-high traffic gene may be a biomarker of mortality in severe COVID-19 patients, as increased expression of this gene was significantly correlated with mortalities ( 414 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in terms of individual genes in the turquoise module, we identified hub-high traffic genes such as UTP14A ( 398 ), RUVBL2 ( 139 ), PRKCD ( 280 , 399 ), KEAP1 ( 400 402 ), CEBPA (TF) ( 403 ), RPL26L1 ( 404 ), PTPN6 ( 255 ), PPARA (TF) ( 405 ), TNFRSF1A ( 406 408 ), IKBKB ( 275 , 409 ), TFEB (TF) ( 410 , 411 ), PSMD4 ( 412 ), and ARHGAP1 ( 413 ), important components in immunopathogenesis of SARS-CoV-2. For example, the TNF receptor superfamily member 1A ( TNFRSF1A ) hub-high traffic gene may be a biomarker of mortality in severe COVID-19 patients, as increased expression of this gene was significantly correlated with mortalities ( 414 ).…”
Section: Discussionmentioning
confidence: 99%
“…5 The mechanisms underlying angiogenesis in COVID-19 remain to be determined. Tan et al 29 reported on elevated angiogenic cytokines, eg, vascular endothelial growth factor (VEGF) and hepatocyte growth factor (HGF) in COVID-19 patients. Other factors, including PGRN, VCAM-1, and trace elements, such as copper, are also found to have a profound impact on angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…They studied myeloid impairment independently for each cell (243). Finally, Tang et al analyzed the origin of cytokine release on balf and pbmc samples (244). Moreover, all the previous studies had different perspectives correlating the airway and blood compartments, and centered their study in one cell-type.…”
Section: Discussionmentioning
confidence: 99%